Epidemiological typing of methicillin-resistant Staphylococcus aureus isolates from surgical wounds and other sites of patients in the Medical centre Ljubljana - Müller-Premru, Manica (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2004)
Background. Methicillin-resistant Staphylococcus aureus (MRSA) frequently causes colonisation and infection of wounds and other sites in hospitalised patients. It evolved by the acquisition of the chromosomal gene mecA in a previously susceptible Staphylococcus aureus (MSSA). This gene encodes a novelpenicillin-binding protein PBP 2a, with a low affinity for methicillin and all other R-lactam antibiotics. Materials and methods. Fifty-two MRSA isolates: 36 from surgical wounds and 16 from other sites (2 from blood, 9 from drains and 5 from intravascular catheter tips) of patients at Departmentsof Surgery of the Medical Centre Ljubljana, Slovenia, were typed bypulsed-field gel electrophoresis (PFGE) of chromosomal DNA to determine the number and distribution of clones. Results. MRSA isolates belonged to 6 genotypes or clones (A-F); 46 to clone A, which was epidemic and 6 to clones B-F. In surgical wounds 31 of 36 MRSA belonged to clone A and 5 to other clones (clones B, C, D, E and F, one isolate each). In other sites 15 of 16 isolates belonged to clone A and one to clone C. Discussion. Epidemic MRSA clone A, which is genetically related to the South German clone, was prevalent. Other MRSA clones were found sporadically in wounds, but almost notin other sites. Some of them could belong to the other internationally spread clones, but in others, horizontal spread of genes from MRSA to MSSA could have occurred.
Keywords: dermatologija; DNA bakterijska; Dna, Bacterial; Electrophoresis, Gel, Pulsed-Field; Elektroforeza gelska, pulzirajoče-polje; Epidemiology; Genetics; infekcije; Isolation And Purification; Kirurška rana, infekcija; Methicillin Resistance; Meticilinska rezistenca; rane; rezistenca; Stafilokokne infekcije; Staphylococcal Infections; Staphylococcus Aureus; Surgical Wound Infection; therapy; zdravljenje